Peningkatan Pengetahuan Usaha Mikro Bagi Nasabah Bank Wakaf Mikro Al-Fadlu Kendal Di Kecamatan Brangsong - Nurifa Laksmitasari Azizah; Eka Kurnia Patmasari; Sherli Junianingrum; Haifa Hannum Arija; Andanawarih, Parasdya Pandhu (Jurnal AbdiMas Ekonomi Terapan, 2024)
This service aims to disseminate knowledge about increasing knowledge of micro businesses in order to increase micro business income. The approach used uses material lecture methods and simulations to introduce micro business knowledge in order to be able to increase income, both in terms of marketing management and in terms of financial management. This community service is expected to provide insight and knowledge to customers. Customers of the Al Fadlu Kendal Micro Waqf Bank, Brangsong District, can also understand how important it is to increase knowledge of micro businesses, especially in MSMEs, to increase income in the future to become a successful micro business that has wide-reaching prospects.